SINEMA VIRTUAL REALITY: MENGGUGAT TATA BAHASA SINEMA - Zamroni, Muhammad (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
Virtual reality cinema is a film with the latest technology which allows viewer “present” in film both consciously and subconsciously. 360 degree vision to the reality that offered by virtual reality technology makes viewers can choose their angle, size, and visual movement which are desired within enjoying the story of film. This study discuss about influence of virtual reality cinema on the possibility grammar of cinema along with aesthetic dimension it produce in the film. This study uses analytic approach against the phenomenon of the emergence of virtual reality cinema, which is considered to be able to change aesthetic of film dimension and grammar of film (cinematography) as an important element in the visualization of a film.Conclusions obtained in this study is changes in aesthetic dimensions and grammar of film that has been understood, which is caused by the presence of virtual reality cinema. Cinematography as a grammar of film is expected to adapt to technological developments or still gives limit as an entity which different and not dependent on technological development.